PENGARUH EMERGENCY TRAINING TERHADAP PENGETAHUAN, SIKAP, DAN PRAKTIK MEDICAL FIRST RESPONDER PADA KESIAPSIAGAAN BENCANA DI KOTA DENPASAR - Pramayanti Putri Sayu Made Ardhia; Purwadhi Purwadhi; Handayani Nining (Journal of Innovation Research and Knowledge, 2025)
Indonesia is one of the countries prone to disasters. Most areas in Indonesia are at high risk of natural disasters. This is due to the geographical, geological, hydrological, social, and demographic conditions of Indonesia. Fast and appropriate first aid for disaster victims is very important to anticipate further severity of injuries. MFR (Medical First Responder) is a trained first responder who first arrives at the scene to provide medical treatment in emergency situations before the victim is taken to a health facility. MFR is part of the public service program in terms of disaster preparedness in each region. The factor that supports success in disaster management is disaster management activities. Emergency training is a training program that aims to provide knowledge, skills, and understanding to SPGDT personnel in responding to emergency situations, so that they can take appropriate steps to protect lives, minimize losses, and restore security and normal conditions after an emergency occurs. This study aims to determine the effect of emergency training on the knowledge, attitudes, and practices of medical first responders in disaster preparedness in Denpasar City. This type of research is quantitative research with 63 respondents. This study used an instrument in the form of a Knowledge, Attitude, Practice of Disaster Management (KAP-DM) questionnaire with 42 questions. The data collection technique used purposive sampling. The data analysis method in this study used the Wilcoxon test using SPSS tools. The results of the bivariate analysis obtained p = 0.01 in knowledge, p = 0.03 in attitude, and p = 0.03 in medical first responder practices after being given emergency training. The results of the study concluded that emergency training has a significant influence on the knowledge, attitudes, and practices of medical first responders in disaster preparedness in Denpasar City.